Separation of growth hormones and sugars in coconut water using micellar-enhanced ultrafiltration - del Rosario, E. J. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2005)
Ultrafiltration (UF) is a pressure-driven separation process wherein small molecules permeate through a semi-permeable membrane while solute molecules of high molecular weight (MW) are retained in the feed stream. Addition of a surfactant above the critical micelle concentration (cmc) allows retention of small molecules by entrapment in micellar aggregates, which do not pass through the membrane. This modified process is called micellar-enhanced ultrafiltration (MEUF). Two sets of polyamide (PA) ultrafiltration (UF) membranes were prepared from a polymeric mixture of 31.5% polycaprolactam (nylon 6), 1% H 2SO4, 40% HCl, 25% water and 2.5% ethanol. The pinhole-free membranes, which were 0.2 mm thick, were characterized in terms of water flux, molecular weight cut-off and membrane fouling. The prepared PA membranes were used to concentrate the growth hormones (GH) of coconut water through MEUF in the presence of a zwitterionic, cationic or anionic surfactant by means of a tangential-flow UF set-up. Betaine, cetylpyridinium chloride (CPC) or sodium dodecyl sulfate (SDS) was the added surfactant. The highest value of the rejection coefficient σ was 99% for SDS at the critical micelle concentration (cmc) of 0.008M; maximal σ values were 95.5% and 86.0% for betaine and CPC, respectively, at their corresponding cmc values. Quantitation of the GH was done by thin-layer chromatography and verification was done using the mungbean (germination) bioassay method; indole acetic acid and kinetin were employed as standards. The results showed that through MEUF, the GH of coconut water were concentrated in the retentate. Based on the mungbean hypocotyl lengths, the highest concentration of GH in the retentate was observed in the presence of either 0.05 M betaine or 0.015 M CPC. UF membranes were also prepared at different ratios (20-25% w/v) of cellulose acetate (CA) to N,N-dimethylformamide and used to recover sugars and growth hormones in coconut water by means of MEUF in the presence of SDS. Maximal σ values (>75%) were obtained above the cmc (0.008M) of SDS using membranes prepared from 25% CA. Permeate fluxes greater than 70 Lm-2h-1 were obtained with 25% CA membranes at 0.35 MPa trans-membrane pressure in a tangential-flow UF module. The permeate flux varied inversely with CA content of the membrane and increased proportionately with trans-membrane pressure. Maximal σ values (>84%) for growth hormones were observed at SDS concentrations above the cmc. Ultraviolet spectral curves were used qualitatively to test for growth hormones in the samples. The bioassay results showed that the growth hormones were concentrated by MEUF most effectively above the cmc of SDS.